Multiple Brain Abscesses Secondary to Odontogenic Infection: A Clinical Case Report - Frisso, Paulo Lucas Capelini; Ellakkis, Richam Faissal El Hossain; Silva, Elton Gomes; Farina, Edgar Manuel Garcete; Sarraf, Raymond Assad El (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Introduction Cerebral abscess is a suppurative infection of the cerebral parenchyma, which may occur due to contiguity, hematogenous dissemination of distant foci, secondary to open traumatic brain injuries, or be idiopathic.Clinical Case A 63-year-old male patient sought assistance due to a severe headache in the frontal region associated with chills and lack of appetite that started four days before. Clinical examination of the patient showed no significant changes. Imaging and laboratory tests on admission showed only nonspecific changes, such as leukocytes 18,540, platelets 517,000, and c-reactive protein 2,0. In such case, magnetic resonance imaging (MRI) of the skull was performed with contrast, showing the presence of expansive lesions compatible with multiple brain abscesses in the right parieto-occipital region.Discussion After excluding the main focus of hematogenous dissemination and in view of the identification of the agent Streptococcus intermedius by means of secretion culture collected through a surgical method, the hypothesis of abscess due to contiguous dental pyogenic foci was pointed out.Conclusion Dental evaluation showed multiple foci of infection with periodontitis and dental abscess, which were treated along with the use of antibiotics directed to the etiologic agent.
Keywords: cerebral abscess; dental infection; Streptoccocus intermedius